2009
DOI: 10.1007/bf03346610
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intermittent treatment with human parathyroid hormone 1–34 in SAMP6 senescence-accelerated mice

Abstract: We examined trabecular and cortical bone in the senescence-accelerated mouse prone 6 (SAMP6) murine model of senile osteoporosis after treatment with human PTH 1-34. Sixteen-week-old female SAMP6 mice were assigned to control and PTH groups. PTH (20 microg/kg) was administered sc 3 times a week for 12 weeks. The control mouse strain, senescence-accelerated mouse resistant 1 (SAMR1), was used for comparison. The femoral metaphysis and diaphysis were used to measure bone mineral density (BMD), analyze the trabec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
3
1
0
Order By: Relevance
“…This is similar to studies with PTH in other mouse models, which show approximately a 10% increase in cortical bone ultimate force with PTH [50, 51]. Our study showed a comparable increase in femoral ultimate force of approximately 8%, though the difference was not significant.…”
Section: 1 Discussionsupporting
confidence: 89%
“…This is similar to studies with PTH in other mouse models, which show approximately a 10% increase in cortical bone ultimate force with PTH [50, 51]. Our study showed a comparable increase in femoral ultimate force of approximately 8%, though the difference was not significant.…”
Section: 1 Discussionsupporting
confidence: 89%
“…Cortical bone did not display the marked changes with bbPTH treatment that were observed in trabecular bone. This is similar to studies with PTH in other mouse models, which show approximately a 10% increase in cortical bone ultimate force with PTH (Washimi, et al, 2010, Zhou, et al, 2003. Our study showed a comparable increase in femoral ultimate force of approximately 8%, though the difference was not significant, and no change was detected in stress or modulus of toughness.…”
Section: Discussionsupporting
confidence: 89%
“…As expected, bbPTH improved many skeletal outcomes in wild type mice as compared to vehicle-treated wild type mice, consistent with literature administering PTH analogs to healthy mice (Washimi, et al, 2010, Lippuner, et al, 2004, Frost, 1999, Kanis, et al, 1994, Lane and Yao, 2010. bbPTH treated mice showed improvements in force to failure, and moments of inertia, indicating an improved cortical structure consistent with increased strength.…”
Section: Bbpth Vs Vehicle: Wild Type Micesupporting
confidence: 86%
“…SAMP strains are categorized into 11 groups according to the senile diseases that they develop naturally, such as senile amyloidosis (SAMP1, 2, 7 and 11), temporomandibular disorders (SAMP3), senile osteoporosis (SAMP6), learning and memory impairments (SAMP8 and 10) and cataract (SAMP9) (15)(16)(17). The SAMP6 strain presents decreasing BMD from the age of 16 weeks, and has a lifespan of ~32 weeks (18). In order to assess the effects of various drugs affecting BMD, additional approaches to reduce BMD must be taken in the SAMP6 strain.…”
Section: Introductionmentioning
confidence: 99%